The Systematic field survey of the Neolithic Site of Graduša – Lokve Project (Archaeologia Adriatica, 2023)
When it comes to the Middle and Late Neolithic site of Graduša – Lokve in Islam Grčki (northern Dalmatia), many questions remain unanswered. The site size and boundaries, the spatial, stratigraphic and cultural correlations between the Middle and Late Neolithic settlements, as well as the correlation between surface findspots and the Neolithic settlement structures identifiable on the surface, are just some. To provide answers to a number of these questions, a systematic field survey was conducted in February 2023. The survey results contribute to a better understanding of the site and will serve as the basis for planning its future excavations.
Keywords: systematic field survey; Graduša – Lokve; Islam Grčki; Middle Neolithic; Late Neolithic